Development Of Carrots (Daucus Carota L.) Flour Steamed Brownies - Arum Dwi Agustin; Ratih Purwasih; Pelangi Pagi Kalimasadha (Poltekkes Kemenkes Surakarta, 2022)
Background: Carrots production in Indonesia is quite abundant but has not been used optimally. How to process carrots is very necessary so that they become foods that have a high selling value while maintaining the content of antioxidant compounds contained therein One way to optimize is to make carrot flour that can reprocess into food products, steamed brownies. This research was conducted to increase the selling value of carrots, to determine the quality and antioxidant activity of carrot flour steamed brownies. Methods: The research type is quantitative with a design of descriptive research. Determination of the quality of carrots flour and carrots flour steamed brownies included water and ash content assays. A qualitative assay using color reaction assays, quantitative analysis, and antioxidant activity using UV-Visible Spectrophotometry. Results: The quality assay result content of water and ash in carrots flour was 4.1% and 0.5% and in carrots flour steamed brownies was 26.8% and 1.8%. A qualitative assay using a color reaction assay with antimony trichloride showed positive results, both for carrot flour and carrot flour steamed brownies. The result of antioxidant activity with IC50 values of 241.4822 ± 2,1294 ppm Conclusion: The quality assay results in carrots flour and carrots flour steamed brownies in accordance with the flour parameters of SNI 3751: 2009 and SNI 01-3840-1995 for steamed brownies. The result of antioxidant activity for carrots flour steamed brownies including a medium level. It is necessary to carry out proximate tests such as fat, protein, carbohydrate, and microbiological tests on carrot flour and carrots flour steamed brownies.